Genetic diversity of provenance and progeny trials of Tabebuiarosea (Bertol.) D.C. stablishedin Chinchiná-Caldas, Colombia (Revista de Investigaciones Universidad del Quindío, 2010)
The objective of this work is to evaluate the genetic biodiversity of the species Tabebuiarosea by the provenance and progeny trials established by Cenicafé in Chinchiná–Caldas, Colombia. To achieve this objective it was conducted a procedure of collection of young leaves of 9individualsforeachoffspring, selecting randomly 3 of the central tree of each one of the 3blockswheretheprogenyareplanted. The leaves were enfleuragedin liquid nitrogen and homogeneously mixed forDNAextraction.In this operation, the itwasusedtheAFLP molecular markers with the combinations E-AAC×MCTG, E-ACT×M-CATyE-AGC×M-CTG. Fromthisoperation resulted a total of 172 bands, 5 of each were monomorphic and 83 were only from1ofthe8 progeny evaluated. Itwasalsoobtained group with range of similarity that has varied from 0.35-0.59, which suggests that the materials evaluated had a considerable high genetic biodiversity, which makes them fit for the genetic upgrade work. It was also assumed that there is similarity between the genetic heap of the progenitors ofCentralAmericaand the only existent Colombian progenit or present in this study. This factmightbedue to the fact that these edsthatoriginated the studied trees were collected in countries located inside the area of the natural distribution of this species. The results obtained are essential to initiate the program of genetic upgrade of this specie and they provethe necessity of including a higher number of Colombian progenies in the assays conducted by Cenicafé.
Keywords: Tabebuia Rosea; provenance and progeny trials; genetic diversity; AFLP